Kosmologi Quadripartit sebagai Kearifan Lokal Minahasa dalam Menjaga Harmoni Alam - Fabylio Cornelius Togas; Marcelino Fransiskus Lomboan; Brigita Gratia; Barnabas Ohoiwutun (Bina Nusantara University, 2026)
Minahasan culture emerged through a long historical process that integrated cosmic mythology with geographical adaptation. These two elements became the foundation and starting point for the development of Minahasan culture as it exists today. As a society with a profound connection to the natural environment, the Minahasan people developed a system of local wisdom that perceives space not merely as a geographical entity but as a cosmological manifestation. One of the expressions of this wisdom is the way the Minahasan people preserve nature through the cardinal directions, embodied in the Quadripartite pattern. This study examines the philosophy of nature in Minahasan society through the quadripartite environmental division, or the concept of the four cardinal directions. Employing a descriptive qualitative method and an ethnophilosophical approach, the study finds that the fourfold pattern of spatial organization represents the Minahasan people's effort to establish harmony between the microcosm (human life) and the macrocosm (the universe). The findings further reveal that the quadripartite concept embodies profound local wisdom, in which each cardinal direction symbolizes the cycle of life, ecological balance, and spiritual responsibility. The Quadripartite model functions not only as a system of spatial orientation but also as a moral and ecological compass that sustains the harmonious relationship among human beings, nature, and the ancestors in the land of Minahasa.